Low-Ion-Dose FIB Modification of Monomicellar Layers for the Creation of Highly Ordered Metal Nanodot Arrays - Mela, Petra; Gorzolnik, Blazej; Bückins, Matthias; Mourran, Ahmed; Mayer, Joachim; Möller, Martin (Small (Weinheim an der Bergstrasse, Germany), 2007)
Creative writing: A low‐dose focused ion beam (FIB) is used to inscribe a pattern onto a monolayer of self‐assembled block‐copolymer/transition‐metal hybrid micelles to create arrays of gold nanodots. FIB lithography combines two different functional elements: hexagonally ordered nanodots created from the resist (see picture, right) and an underlying grating, which makes the nanodot arrays visible by optical microscopy (left).